Synthesis of semiconductors of different compositions and their absorption capacity in the UV-A region - Silva, Luana Góes Soares da; Alves, Annelise Kopp (Brazilian Journal of Science, 2023)
Photocatalysts are semiconductor solids that are characterized by converting the energy contained in photons (light) into electrochemical energy available in a chemical system, both for oxidation and for the reduction of chemical compounds or species (ions). The application of TiO2 in heterogeneous photocatalysis acquires relevance due to its efficiency in the decomposition of water and air pollutants, bacteria, cancer cells and in the degradation of toxic organic compounds. Thus, this work aimed to synthesize by electrospinning TiO2 and TiO2 fibers doped with H2WO4 or Na2WO4.2H2O. These samples were heat treated between 650 ºC and 800 ºC. Characterized as: scanning electron microscopy (SEM) morphology, X-ray diffraction (XRD) crystalline phases, and photoactivity by degradation tests of 125 mL of a 20 ppm solution of methyl orange dye. The results show that the TiO2/Na2WO4.2H2O (800 ºC) sample is more effective in dye degradation, possibly due to the existence of a synchronicity between the chemical and physical properties of titanium and tungsten oxides and the formation of O2 vacancies.